Long-term characteristics of marine heatwaves (1982–2021) in Indonesian water and their impact on upwelling (case study: Southern Java) - Ningsih, Nining Sari; Beliyana, Erlin; Kamila, Ikliema Hassya; Tarya, Ayi (Frontiers in Marine Science, 2025)
Intense and prolonged marine heatwaves (MHWs) have been observed in the Indonesian seas over the past 40 years (1982–2021). The frequency and duration of MHWs have increased, while their maximum intensity has declined, reflecting the impacts of global warming. This study analyzed intense MHWs in six key regions: Western Sumatra, Southern Java, Java Sea, Makassar Strait, Maluku Sea, and Northern Papua. A heat budget analysis revealed that heat advection is the primary driver of sea surface temperature warming and MHW events in Southern Java and Western Sumatra, whereas entrainment played a more significant role in other regions. Cross-correlation and scatter plot analyses further indicated that the El Niño-Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) also played a crucial role in MHW formation. Notably, MHW occurrences were more frequent during ENSO phases than IOD phases, suggesting ENSO’s stronger influence. Among all study regions, Southern Java exhibited the highest correlation between MHW intensity and both the Oceanic Niño Index and the Dipole Mode Index, underscoring the significant influence of ENSO and IOD in this area. From June to August 1998 to 2021, upwelling intensity in Southern Java weakened due to acute MHW events, with the strongest suppression occurring in the eastern part of the region compared to its central and western areas. These extreme and persistent oceans warming events pose a growing threat to marine ecosystems and fisheries, underscoring the urgent need for further research and mitigation strategies.